PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VII SMPN 1 ENAM LINGKUNG - Meri Marliana (Jurnal Edukasi dan Penelitian Matematika, 2022)
Understanding the concept becomes the main basis in the achievement of learning mathematics. However, mathematics learning at SMPN 1 Enam Lingkung has not shown ability to understand students mathematichal concepts. Therefore, a apply the Student Teams Achievement Division (STAD) cooperative learning type model to see its effect on understanding of students in mathematical concepts.  The research type used is a quasi-experimental study and the posttest only design with nonequivalent groups. Based on data analysis using t-test, it can be concluded that the understanding of the concepts of students who learn with the Student Teams Achievement Division (STAD) model is more good than students who learn with the direct learning model in class VII SMPN 1 Enam Lingkung. Keywords– Teams work, Understanding Mathematical concepts, Student Teams Achievement Divison (STAD) Model, Mathematics Learning